Industrial Competitiveness and Diffusion of New Pollution Abatement Technology - a new look at the Porter-hypothesis - Mads Greaker (Statistics Norway, Research Department, 2004)
We study the relationship between industrial competitiveness, adaption of cleaner production techniques and environmental policy. While other contributions have analyzed environmental innovations with point of departure in the polluting firm, we introduce an up-stream market for new pollution abatement technology. A strong environmental policy may then benefit industrial competitiveness through its effect on the price on pollution abatement. However, the incentive for a stringent policy partly disappears if there is a global market for pollution abatement solutions, and environmental policy is set simultaneously in several countries. In our analysis we hope to draw attention to an often overlooked issue. The diffusion of new pollution abatement techniques often requires a new market to develop. If policy is lax, few firms enter and may charge a high mark-up to cower entry costs. On the other hand, a stringent environmental policy induces higher demand and allows a lower mark-up. Consequently, even if the polluting industry in question is export oriented, a stringent policy may be welfare enhancing
Keywords: H7; Q2; R3; 330; Strategic Environmental Policy; Eco-dumping; Porterhypothesis